Color Rendering of Images in the Internet and Print Reproductions of the Sistine Chapel's Frescos. Issue 1 (2nd April 2016) - Szücs, Veronika; Sik-Lányi, Cecília
ABSTRACT: Many digital reproductions of artefacts can be found on the Internet. In this study we investigate differences between original works of art and digital reproductions downloaded from several online databases. Four frescos in the Sistine Chapel were selected for detailed investigation. Representative colored patches were measured on these reproductions from the Internet and from two printed albums. These data were compared with the Vatican Museum's measurements of the original frescos and measurements in the Sistine Chapel taken by the researchers of the Virtual Environments and Imaging Technologies Laboratory of the University of Pannonia. Results presented in this article demonstrate that there are significant differences between the original artefacts and their digital reproductions. The source of these differences is very complex. One is the difference between the displaying techniques of different web browsers, which produces relevant aberrations in color rendering. Differences can also arise from the JPEG encoding and decoding methods. Implicit use of color spaces in browsers, missing or incorrect EXIF data, and noncalibrated displays together can result in very different forms of representation.